Antimicrobial Lactoferrin Peptides: The Hidden Players in the Protective Function of a Multifunctional Protein. (10th March 2013) - Sinha, Mau; Kaushik, Sanket; Kaur, Punit; Sharma, Sujata; Singh, Tej P.
Abstract : Lactoferrin is a multifunctional, iron-binding glycoprotein which displays a wide array of modes of action to execute its primary antimicrobial function. It contains various antimicrobial peptides which are released upon its hydrolysis by proteases. These peptides display a similarity with the antimicrobial cationic peptides found in nature. In the current scenario of increasing resistance to antibiotics, there is a need for the discovery of novel antimicrobial drugs. In this context, the structural and functional perspectives on some of the antimicrobial peptides found in N-lobe of lactoferrin have been reviewed. This paper provides the comparison of lactoferrin peptides with other antimicrobial peptides found in nature as well as interspecies comparison of the structural properties of these peptides within the native lactoferrin.